Acceptance of advanced radiation therapy in a remote new radiotherapy facility of central India: an analytical observational study - Ghosh, Gopa; Patel, Ganesh; Agarwal, Ankit; Goenka, Aniket; Jain, Rashmi (International Journal of Research in Medical Sciences, 2024)
Background: For more than 50% of cancer cases requiring radiotherapy, some 500-odd radiation facilities in India widely cater to urban areas and big towns. Few studies indicate that one of the potential strategies to limit geographic disparity is to build cancer centers in areas of need or to develop compact fully mobile linacs to facilitate access of rural population and reduce travel. This study was designed to evaluate feasibility of an advanced radiation center at the block/tehsil level, asses acceptance of new technologies, evaluate compliance to treatment in terms of daily attendance and treatment breaks, compare total duration of treatment among various techniques. Methods: Histopathologically proven cancer cases from May 2016 to December 2022 reported in a new tehsil-level tertiary radiotherapy facility in central India were included in this observational study. Results: Total of 2869 cases from various sites were evaluated and advised to be treated with radiotherapy in the department of radiation oncology from May 2016 to December 2022. Over a while shift in trend from 3D CRT to IMRT with image guidance and from 2021 few cases of SBRT to metastatic sites have been observed amongst physicians and patients with reduced toxicity along with improved patient compliance. Conclusions: Advanced radiation treatment at semi urban/tehsil level is well accepted and feasible.